Analysis of The Effect of Problem Based Learning on Mathematical Problem Solving Abilities Based Gender at SMP Negeri 1 Rantau Selatan - Sri Endang Wahyuni (Prodi Pendidikan Matematika FMIPA Universitas Negeri Medan, 2021)
This study aims to : 1) describe what the students mathematical problem solving ability using problem based learning model better than using conventional method, 2) describe the differences in the mathematical problem solving ability between male and female using the problem based learning model. This research uses quantitative research. Type of research is a semi experiment/quasi experiment. This research conducted in SMP Negeri 1 Rantau Selatan, Labuhanbatu. The time of research conducted on second semester academic year 2020/2021. The research instrument instead to obtain a valid instrumen like validity test and realibility test. The result of the research are the mathematical problem solving ability of students who are taught using a problem based learning model is better than students who are taught using a conventional learning method. The mathematical problem solving ability of students who are taught by problem based learning model in female is better than the mathematical problem solving abilities of students in male. Gender can not affect to mathematical problem solving ability with uses problem based learning and conventional method